Risk factors for acute kidney injury in children with critical illness - Chalisah, Lilis; Sovira, Nora; Amna, Eka Yunita; Anidar, Anidar; Haris, Syafruddin; Bakhtiar, Bakhtiar (Indonesian Pediatric Society, 2024)
Background Acute kidney injury (AKI) is an acute functional kidney disorder that increases morbidity and mortality in children. The mortality rate for critically ill patients accompanied by AKI is quite high and is influenced by the degree of AKI, the severity of the disease, and organ function disorders. Understanding the risk factors of developing AKI in children with critical illness can help prevent AKI. Objective To determine the risk factors for AKI in children with critical illness. Methods This retrospective cohort study included 255 children aged 1 month to 18 years admitted at the pediatric intensive care unit (PICU) of dr. Zainoel Abidin Regional Public Hospital, Banda Aceh, Aceh, from January to December 2022 using medical record data. Bivariate and multivariate analyses were performed. Results Acute kidney injury occurred in 68 (26.7%) patients. Based on pRIFLE criteria, 34 (50%) patients had AKI in the failure stage. Risk factors for AKI in children with critical illness were in descending order of RR: sepsis (RR 14.3; 95%CI 11.68 to 18.66; P=0.000), mechanical ventilation (RR 12.13; 95%CI 8.75 to 15.98; P=0.000), respiratory disorders (RR 2.51; 95%CI 2.06 to 4.02; P=0.003), congenital heart disease (RR 2.08; 95%CI 2.00 to 3.05; P=0.004), CNS disorders (RR 1.24; 95%CI 1.02 to 2.49; P=0.048), nephrotoxic drug use (RR 1.41; 95%CI 1.24 to 3.08; P=0.000), and age 1 month to 5 years (RR 0.072; 95%CI 0.16 to 0.32; P=0.010). Conclusion Sepsis is a risk factor for AKI in children with critical illness, followed by mechanical ventilation use, respiratory disorders, nephrotoxic drug use. Age <5 years is a protective factor.